Fly ash as supplementary material in concrete: a review - Zeggar, Mohamed Lamine; Noor Azline; Safiee, N. Azizi (Institute of Physics Publishing, 2019)
The use of supplementary cementitious materials such as fly ash has seen a steady growth among the recent studies as an economical and effective solution for partial cement replacement. A challenging issue when replacing cement is that the supplementary materials affect concrete properties differently according to various factors such as: the grade of cement, the percentage of replacement, curing periods and environment condition. In order to determine how the concrete compressive strength and its rheological properties can be affected by fly ash, a review on the previous study on concrete fly ash mixtures subjected to various experimentation factors in terms of its main properties has been carried out. The outcomes showed that low calcium fly ash content increases concrete compressive strength of hardened concrete for a period ranging between 28 to 56 days and enhances the concrete rheological properties when the substitution percentage is not too high. Consequently, when fly ash is used as a substitute of cement with a medium quantity, it has an economical and sustainable effect on the cement and concrete industry.